Counter-urbanisation in pre-pandemic times: disentangling the influences of amenity and disamenity. Issue 4 (2nd October 2022) - Argent, Neil; Plummer, Paul
ABSTRACT: The COVID-19 pandemic has stimulated a resurgence in counter-urbanisation in Australia with ex-urban populations leaving behind the perceived disamenity of city life for simpler, cheaper and lockdown-free lives. This article investigates the drivers of in-migration and net migration into non-metropolitan New South Wales from the metropolitan zone between 2011 and 2016, focusing on the potential draw of rural amenity, together with the potential 'push' factors of urban disamenity. The results show that non-metropolitan NSW is becoming less dependent on counter-urbanisation flows from Sydney, while simultaneously seeing stronger net migration gains from interchanges with the broad metropolitan zone. Hypothesis testing upheld the contention that rural amenity accounted for a statistically significant share of the variance in in-migration - and net migration - from Sydney. However, the hypothesis that Sydney's perceived disamenity is leading to out-migration flows and net migration losses was not well supported, confounded by mis-specification issues. High population densities are associated with out-migration from the Sydney region to all categories of settlement within the remainder of NSW and Australia. However, changes in density are only a strong and reliable influence on net migration within the broad Sydney metropolitan area but the direction of that influence is positive rather than negative. The article reveals that the proportion of immigrants within a metropolitan local government area population is negatively associated with out-migration.